2007
DOI: 10.3171/foc.2007.23.5.16
|View full text |Cite
|
Sign up to set email alerts
|

Vision loss after spine surgery: review of the literature and recommendations

Abstract: HE focus of this review was to present the issue of vision loss associated with modern spinal surgery. Vision loss after spinal surgery is a unique complication of optic nerve damage resulting from ION, most often located in the posterior portion of the orbital optic nerve. This is surprising because the posterior area is rarely affected by ischemia. Such "posterior" lesions are designated PION. They have been uncommon until recently, mostly found in association with lumbar spinal surgery. We present the uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 39 publications
(61 reference statements)
0
41
0
1
Order By: Relevance
“…This information might be useful for spine surgeons and anesthesiologists. Although post-operative stroke rarely happens in lumbar spinal surgery, it is repeatedly reported with various kinds of manifestations including blindness, weakness, impaired cognitive function, or even death [6][7][8][21][22][23][24][25][26]. Patients with spinal diseases usually need to pass a series of cardiac and pulmonary evaluations before being considered as candidates for spinal surgery, especially if they are old or have risk factors for cerebrovascular or heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This information might be useful for spine surgeons and anesthesiologists. Although post-operative stroke rarely happens in lumbar spinal surgery, it is repeatedly reported with various kinds of manifestations including blindness, weakness, impaired cognitive function, or even death [6][7][8][21][22][23][24][25][26]. Patients with spinal diseases usually need to pass a series of cardiac and pulmonary evaluations before being considered as candidates for spinal surgery, especially if they are old or have risk factors for cerebrovascular or heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is a unique case, in that most other reports on POVL show patients who do not improve after suffering this devastating complication [1,4,[11][12][13]. Our patient had transient POVL, which resolved completely within 48 h. ION occurs after an ischemic insult to the optic nerve and can be divided into anterior ischemic optic neuropathy (AION) and PION depending on the location of the lesion [14].…”
Section: Discussionmentioning
confidence: 84%
“…Baig and colleagues [8] projected a 0.2% incidence of POVL in spine procedures and .05% of all cases. Contributing medical conditions were hypertension (41%) and diabetes (16%).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Baig and colleagues [8] reviewed POVL caused by PION after spine surgery. They suggested that the posterior optic nerve may be susceptible to decreased perfusion caused by increased venous pressure.…”
Section: Literature Reviewmentioning
confidence: 99%